Immature platelet fraction related parameters in the differential diagnosis of thrombocytopenia. (17th August 2020) - Li, Junxun; Li, Ying; Ouyang, Juan; Zhang, Fan; Liang, Chujia; Ye, Zhuangjian; Chen, Shaoqian; Cheng, Jing
Abstract: The pathogenesis of thrombocytopenia can be divided into increased destruction (ID) of platelets in the peripheral blood and decreased production (DP) of platelets in the bone marrow. This study aimed to analyze the efficacy of immature platelet fraction (IPF) related parameters, including the IPF count (IPF#), IPF percentage (IPF%) and highly fluorescence IPF percentage (H-IPF%), measured by XN-9000, in the differential diagnosis of thrombocytopenia. One hundred and twenty healthy volunteers were enrolled in the healthy control (HC) group, and 180 thrombocytopenia patients were grouped into either the increased destruction (ID) group or the decreased production (DP) group according to their final diagnosis. IPF# was significantly lower in the DP group than in the ID and HC groups ( P < .01). Among the three groups, the ID group had the highest IPF% and H-IPF%, and the HC group had the lowest IPF% and H-IPF%. The differences between the three groups were all statistically significant ( P < .01). In differentiating the ID patients from the DP patients, the areas under the operating characteristics curve of IPF#, IPF% and H-IPF% were 0.859, 0.944 and 0.930, respectively. False positive rates were below 0.04 when IPF#, IPF% and H-IPF% were above 2.65, 7.55 and 2.35, respectively. IPF related parameters showed high efficacy in the differential diagnosis of thrombocytopenia. However, due to the small numerical values of the IPF related parameters in some thrombocytopenia patients, the fluctuations of IPF% and H-IPF% should also be taken into consideration. Though H-IPF% is a new parameter, its effectiveness in the differential diagnosis of thrombocytopenia is not better than IPF%'s.